Інтелектуалізація систем менеджменту промислових підприємств - Ситник, Йосиф Степанович (Національний університет "Львівська політехніка", 2018)
Дисертаційна робота спрямована на вдосконалення концептуальних, теоретико-методологічних та прикладних аспектів формування процесу інтелектуалізації систем менеджменту промислових підприємств в умовах становлення інтелектуально-знаннєвої економіки. Розроблено концепцію інтелектуалізації систем менеджменту на основі еволюційного процесу впливу чинників зовнішнього середовища і внутрішнього самоорганізування систем менеджменту та організаційно-функціональну модель механізму інтегрування підсистем (інтелектоносіїв) на засадах інтелектуалізації. Удосконалено механізм розвитку інтелектуальної активності як цільової функції менеджменту персоналу, інструментарій моделювання розвитку особистісно-інтелектуального потенціалу в системах менеджменту. Розроблено метод діагностування процесу інтелектуалізації систем менеджменту та метод рейтингового оцінювання результативності їх інтелектуалізації, що передбачає визначення інтегрального рівня інтелектуалізації менеджменту на підставі кількісної експертної оцінки позиції об’єкта дослідження. Розроблено метод аналізування впливу активаторів інтелектуалізації систем менеджменту підприємств на управління персоналом. Диссертационная работа направлена на совершенствование концептуальных, теоретико-методологических и прикладных аспектов формирования процесса интеллектуализации систем менеджмента промышленных предприятий в условиях становления интеллектуально-знанневой экономики. Разработана концепция интеллектуализации систем менеджмента на основе эволюционного процесса влияния факторов внешней среды и внутренней самоорганизации систем менеджмента и организационно функциональная модель механизма интегрирования подсистем (интелектоносителей) на принципах интеллектуализации. Усовершенствован механизм развития интеллектуальной активности как целевой функции менеджмента персонала, инструментарий моделирования развития личностно интеллектуального потенциала в системах менеджмента. Разработан метод диагностирования процесса интеллектуализации систем менеджмента и метод рейтингового оценивания результативности их интеллектуализации, что предусматривает определение интегрального уровня интеллектуализации менеджмента на основании количественной экспертной оценки позиции объекта исследования. Разработан метод анализирования влияния активаторов интеллектуализации систем менеджмента на управление персоналом. The dissertation work is aimed to improve the conceptual, theoretical, methodological and applied aspects of the process of formation and evaluation of the effectiveness of intellectualization of management systems of industrial enterprises in the conditions of formation of the intellectual-knowledge-economy. Intellectualization of management systems of enterprises is a way to implement a continuous transformation of the elements and structure of management and control this model via synchronization and integration of processes needed for the formation and application of new management approaches, backed up by intellectually-knowledgeable capacity of staff and the system as a whole. Despite the theoretical basis of the process of intellectualization of management systems of enterprises, it is proved that among its components is dominating a human capital and specialized knowledge, personal and organizational intellectual potential, intellectual capital, intellectual property, information and communication technology and other intangible assets. In the context of the processes of intellectualization is developed the essence of the concepts "intellect", "intellectual potential of the enterprise", "intelligent management systems", "management system", "structure of management systems". It is determined the essential-substantial signs of intellectual potential and specified the main components of intellectual capital of enterprises. It is developed a scientific-methodological basis of the concept of intellectualization of systems management an enterprise on the basis of the influence of evolutionary processes in the external environment and increasing activation of the internal self-organization of management systems under the influence of the intellectually-knowledgeable assets and information and communication technologies, which substantiates the key categories of intellectualization, the sequence of its stages, the directions and elements of the model, which covers the objectives, principles, strategies, tactics, methods, functions, tasks, techniques, criteria and indicators of evaluation. It is substantiated that an effective process of intellectualization of the management systems can be implemented based on the definition of and compliance with the fundamental conditions that allow us to create and classify a complex system-forming functional and structural specific principles of intellectualization in the following areas: process and meaningful filling; functional purposes; cognition. It is proposed a classification of the factors which are influencing to the process and the performance of intellectualization of management systems of the enterprises, which lays the foundation for a comprehensive understanding of the various aspects of their characteristics according to the following criteria: conceptual identity; priority; vector of influence on the process of intelligence flow; character of the process promotion; force of influence; interconnections; source of origin; the level of regulation in the management system; role of the factor in induction of management systems; influence on the level of investment in human capital; impact on intellectual activity; proportionality of influence; objective orientation of factors within management systems; the number of variables covered; content. Is developed a toolkit of diagnostics of the process of intellectualization of management systems of enterprises, which provides an opportunity for businesses which begin the process of intellectualization of the management systems is created to identify the starting assumptions and to examine the current level of intellectual and knowledgeable asset of management system, for enterprises that have implemented the intellectualization management systems – to perform diagnostic assessment of the development process based on intermediate, group and integral indexes and shape of the future strategy of intellectualization. A method of rating assessment of the effectiveness of intellectualization of the management systems of enterprises is developed, and is proposed to calculate using the parameter of the integral level of intellectualization of the management systems on the basis of quantitative assessment of the detailed system of indicators, taking into account their weighting factors that should be evaluated on the basis of their groupings for the total criteria (intelligence capacity, intelligence activity, intellect productivity, integration, dynamic management model). On the basis of the range of the modified scale of Harrington the method allows to identify certifications of integrated levels of intellectualization management systems of enterprises in accordance with the linguistic and quantitative scores. In this work are developed theoretical and applied models: diffusion processes, intellectual-knowledgeable achievements in the management system; prediction of the dependence of the amount of motivation remuneration of intellectuals on the total supply of intellectually-knowledgeable product; making the decisions by the participants of intellectually active media management systems (individual and collective conduct in relation to the exercise of certain intellectual-knowledgeable action). The proposed approach allows to extend the scope of application of economic-mathematical modeling for development of the environments of intellectual creation in the management system of enterprises and mentally-functional space of experts regarding business activities of enterprises. A method for the analysis of the impact of activators of intellectualization of the management systems of enterprises in personnel management of industrial enterprises is improved based on the calculation of a number of representative indicators (level of intellectual activity, staff, integral index of the intellectual capital formation, the level of intelligence of net income, the level of remuneration of staff in the payroll for the growth of intellect, the integral index of information and communication technologies, integral level of development the competence of managers, the level of stability of the staff, the integral level of development of organizational culture, integral index of development of management systems) and involves using the tools of multivariable regression modeling.
Интеллектуализация систем менеджмента промышленных предприятий
Intellectualization of the systems of management of industrial enterprises
Keywords: інтелект; система менеджменту; інтелектуалізація; інтелектуально-знаннєві активи; інтегрування; промислові підприємства; індекс; рейтинг; діагностування; управління персоналом; модель управління; интеллект; система менеджмента; интеллектуализация; интелектуально-знанневые активы; интегрирования; промышленные предприятия; индекс; рейтинг; диагностирование; управление персоналом; модель управления; intelligence; management system; intellectualization; intellectual-knowledgeable assets; integration; industry; index; rating; diagnostics; personnel management; management model; 005.336.4:334.716